Communication Problems Faced by Waiters and Waitresses in Serving Guests - Damayanti, Desak Ketut Citra; Suarcaya, Putu; Paramarta, I Made Suta (Association of Islamic Education Managers (Permapendis) Indonesia, North Sumatra Province, 2025)
This study employs a qualitative research design, using observation and interview as collection methods. Observation sheets and interview guidelines served as the main instruments. This study examines types of communication problem and how to handle the communication problem. The findings show that staff faced four to six communication problems, with the first waiter experiencing 50%, the waitress 60%, and the third waiter 40%. From these results, the communication problems faced by three staff were ambiguous or unclear words, problem with listening, distracted concentration, and problem with pronunciation, each of which was experienced equally by all staff. These communication problems are not always caused by the staff themselves, but they can occur due to the crowded situation of the restaurant, the sound of music and the voices of many guests. In addition, the problem occurs due to the factor of guests who cannot speak English and the small voice of the guests. They handle communication problems by using the LEARN model of complaint handling techniques. In addition to applying various communication techniques, staff are also required to bring problems to their manager for appropriate solutions. Communication problems encountered include serving non-English speaking guests with the help of Google Translate and showing photos of the food, as well as dealing with ignorant guests in a professional manner by reconfirming the order until it is correct.